Mitigating Cyber Sexual Harassment via Social Media Platforms - Hero, Eko; Astini, Bunga (Universitas Islam Negeri Raden Intan Lampung, 2024)
The widespread use of social media has led several accounts to utilize these platforms as educational media for cyber sexual harassment (CSH) awareness. This research examines the relationship between motives and satisfaction of followers of CSH educational accounts in Indonesia, analyzing four prominent accounts: @media.riseup, @awaskbgo, @stop.kbgo, and @taskforce_kbgo. This study employs quantitative methods using the Expectancy-Value model introduced by Palmgreen, distinguishing between Gratification Sought (GS) and Gratification Obtained (GO). Data were collected from 100 respondents across Indonesia using proportionate stratified random sampling, with analysis conducted through Spearman Rho correlation and mean difference tests. The sample comprised predominantly female followers (68%) aged 19-25 years, with 52% having experienced cyber sexual harassment. The results demonstrate a significant positive relationship between motives and satisfaction with a correlation value of 0.720 (p < 0.05). However, the mean test reveals a negative satisfaction gap of 0.14 between expected and obtained gratifications, indicating these educational accounts have not fully met followers' expectations. These findings suggest improvements in content consistency and delivery methods are needed to enhance educational effectiveness.